(3GdQSGdI GdTeSjI aj GdbhGYO GdefWbjIs - (3GdcGJHj GdbRhjfj, fLe GdOjf, OHjQGf, Ydj Hf YeQ Hf Ydj, (B675 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj CHOY fXGe GdhLhO (B... (3hQJHJg Ydi ebOeI hKdGK ebGdGJ hNGJeI CeG GdebOeI aajgG HMKGf GdHMK GdChd aj eGgjI GdefWb hHjGf GdMGLI Edjg GdYde CeG JUhQ abW gh MUhd UhQI GdTjA aj GdYbd hJUhQ eYg Mce (B...s
(3BNQgG (B:s
(3GdaUd GdQGHY (B: (3aj GdJYQjaGJ GdeYQa ddTjA gh GdPj jSJdRe JUhQg JUhQ GdTjA Ch GeJjGRg Yf cd eG YOGg hgh dG jLhR Gf jchf HfaS GdeGgjI dCf GdeYQa eYdhe bHd GdeYQa hGdTjA dG jYde bHd faSg (B...(3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\315s
(3cTa GdXfhf (B2\1063s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs